ABDACOM: America’s first coalition experience in World War II - Nelson, Jeffrey C. (Kansas State University, 2012)
On December 7, 1941 the Japanese Empire launched a surprise attack on the United States at the Pearl Harbor naval base in the territory of Hawaii. The following day President Franklin D. Roosevelt declared war on Japan, and America was suddenly an active participant in a global war that had already been underway for over five years. World War II pitted the Axis (Japan, Germany, and Italy) against a coalition of allied nations that were united primarily by fear of Axis totalitarianism. Typically referred to as the Allies, the alliance’s most powerful participants included the United States, the Soviet Union, and Great Britain. However, many other nations were involved on the Allied side. Smaller European countries such as Holland, Belgium, and Poland fought with armed forces and governments in exile located in London after their homelands had been overrun by the Germans in 1939 and 1940. China had been at war with Japan since 1937. After the United States entered the war, allied action resulted in the creation of different, localized military coalitions between 1941 and 1945. These coalitions presented Allied leaders with unique problems created by the political, geographic, military and logistical issues of fighting war on a global scale. The earliest coalition in which the United States was involved was known by the acronym ABDACOM, short for the American, British, Dutch, Australian Command. ABDACOM’s mission was the defense of the Malay Barrier, which stretched from the Malay Peninsula through the Dutch East Indies to New Guinea, and the protection of the Southwest Pacific Area from Japanese invasion. In its brief two-month existence the ADBA coalition in the Southwest Pacific Area failed to prevent the Japanese from taking the Malay Barrier, Singapore, Burma and the islands between Java and the Philippines. This was due not to one overriding problem, but to a combination of planning, command, and logistical problems, compounded by the distance of Allied production and training centers from the front lines. These problems can be traced from the late 1930s to the dissolution of ABDACOM at the end of February 1942. Historians have often overlooked the underlying causes of the United States’ first foray into coalition warfare in World War II. To better understand why the Allied forces succumbed to the Japanese onslaught so quickly, one must look at political, military and economic relations between the United States and its allies prior to the onset of hostilities in 1941. Domestic political realities combined with international diplomatic differences kept the United States from openly preparing for coalition action until the Japanese attack on Pearl Harbor. The ensuing military coalition suffered from numerous deficiencies in command structure and logistics. Though pre-war planning existed within each of the Allied governments, the lack of cooperative action gave the Japanese military an insurmountable military advantage over the members of the ABDA coalition. Given the limited scope of this paper the focus will be on American participation in ABDACOM. The other countries involved will be included insomuch as they help to fill out the story of the United States and its first coalition effort in World War II. The story of the ABDACOM coalition is one of perseverance, creative planning, and deep stoicism in the face of overwhelming odds. The short life of the coalition gave planners in Washington, D.C. and London time to sort out potential conflicts between the Allies.
Keywords: World War II; Coalition; Netherlands East Indies (NEI); American, British, Dutch, Australian Command (ABDACOM); Java; Southwest Pacific; Military History (0722)